Belonging and the politics of belonging - Yuval-Davis, Nira (Patterns of prejudice, 2006)
Yuval-Davis outlines an analytical framework for the study of belonging and the politics of belonging. Her article is divided into three interconnected parts. The first explores the notion of 'belonging' and the different analytical levels on which it needs to be studied: social locations; identifications and emotional attachments; and ethical and political values. The second part focuses on the politics of belonging and how it relates to the participatory politics of citizenship as well as to that of entitlement and status. The third part illustrates, using British examples, some of the ways particular political projects of belonging select specific levels of belonging in order to construct their projects.